2021
DOI: 10.3390/polym13162819
|View full text |Cite
|
Sign up to set email alerts
|

A Negative Index Nonagonal CSRR Metamaterial-Based Compact Flexible Planar Monopole Antenna for Ultrawideband Applications Using Viscose-Wool Felt

Abstract: In this paper, a compact textile ultrawideband (UWB) planar monopole antenna loaded with a metamaterial unit cell array (MTMUCA) structure with epsilon-negative (ENG) and near-zero refractive index (NZRI) properties is proposed. The proposed MTMUCA was constructed based on a combination of a rectangular- and a nonagonal-shaped unit cell. The size of the antenna was 0.825 λ0 × 0.75 λ0 × 0.075 λ0, whereas each MTMUCA was sized at 0.312λ0 × 0.312λ0, with respect to a free space wavelength of 7.5 GHz. The antenna … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Meanwhile, a viscose-wool felt with a thickness of 3 mm, a dielectric constant of 1.44 and a loss tangent of 0.044 was employed as the substrate. Existing EM related works using this felt with Shiedlit Super TM have shown good performance where the simulated and measured results were approximately the same [ 4 , 9 , 18 ]. The felt consists of 70% wool and 30% viscose which forms a good composition of fibers with a density of 0.25 gm/CC.…”
Section: Flexible Polymer-based Meta-wearable Antenna Designmentioning
confidence: 90%
See 2 more Smart Citations
“…Meanwhile, a viscose-wool felt with a thickness of 3 mm, a dielectric constant of 1.44 and a loss tangent of 0.044 was employed as the substrate. Existing EM related works using this felt with Shiedlit Super TM have shown good performance where the simulated and measured results were approximately the same [ 4 , 9 , 18 ]. The felt consists of 70% wool and 30% viscose which forms a good composition of fibers with a density of 0.25 gm/CC.…”
Section: Flexible Polymer-based Meta-wearable Antenna Designmentioning
confidence: 90%
“…The steps were used to fabricate the prototype as shown in Figure 6 . These steps were adopted from the literature that used similar polymer and conductive materials [ 9 , 32 ]. After finalizing the modeling in the simulation, the structures were printed using computer aided design (CAD) software.…”
Section: Flexible Polymer-based Meta-wearable Antenna Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing work [9,10] have also explored the use of flexible materials to design the antennas and, thus, it will be suitable for on-body applications. In addition, previous studies demonstrated that incorporating metamaterials (MTMs) into conventional antenna design resulted in enhancement of antenna's gain bandwidth, higher radiation efficiency, improvement in radiation pattern, and reduction of specific absorption rate (SAR) [8,11,12]. MTMs are artificially-engineered structures which exhibit non-naturally occurring electric and magnetic properties such as negative refractive index [13].…”
Section: Introductionmentioning
confidence: 99%
“…In antenna applications, surface roughness has a negative impact on antenna gain [ 43 ]. Additionally, metamaterials based on split-ring resonators (SRRs), complementary split-ring resonators (CSRRs), capacitance-loaded strips (CLSs), or similar structures can be used to improve high-frequency characteristics [ 44 ].…”
Section: Introductionmentioning
confidence: 99%